Variability among wild common bean lines for traits related with N2 fixation capacity - Andriolo, Jesuíno; Pereira, Pedro Antonio Arraes; Henson, Robert A. (Pesquisa Agropecuaria Brasileira, 1994)
The N2 fixation capacity of 50 wild bean (Phaseolus vulgaris L.) lines were evaluated in the greenhouse. Plants were sampled 50 days after planting and results indicated high variability among wild bean lines for most traits evaluated. The wild bean showed higher number of small nodules than the cultivated bean. Even though most wild bean lines accumulated less dry matter than the cultivated genotypes in the root and aerial parts, four wild bean lines, G 12895, Sel 8-5a, G 12932 and Sel 8-5b, performed as well as or even better on traits related with N2 fixation than Puebla 152, considered a good N2 fixer.